Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

For $k,n \in \mathbb{Z}$ of these integrals: \begin{align} 1) \quad & \int_{-\pi}^{\pi}\cos(nt)\cos(kt)dt \\ 2) \quad & \int_{-\pi}^{\pi}\cos(kt)\sin(nt)dt \\ 3) \quad & \int_{-\pi}^{\pi}\sin(nt)\sin(kt)dt \end{align}

The book says: the relations for 1) is : $\pi$ for $n=k$ greater than 0 , $2\pi $ for $n=k=0$, 0 for $n$ not equal to k ; 2) is always equal to 0 , 3) is $\pi$ for $n=m> 0$ or 0 otherwise

What I have tried to show this:

I calculated with twice partial integration for 1., deriving for the factor with k \begin{align} I:= &\int \cos(kt)\cos(nt)dt \\ = & \frac{1}{n}\sin(nt)\cos(kt)+\frac{k}{n}\int \sin(nt)\sin(kt)dt\\ = & \int \sin(nt)\sin(kt)dt \\ = & \frac{-1}{n}\cos(nt)\sin(kt)-\int\frac{-1}{n}\cos(nt)k\cos(kt)dt \\ \end{align} $$ {\Huge \Downarrow} $$ \begin{align} I = & \frac{1}{n} \sin (nt) \cos(kt)+\frac{k}{n} \left(\frac{-1}{n}\cos(nt)\sin(kt)+\frac{k}{n}I\right) \\ = & \frac{1}{n}\sin(nt)\cos(kt)-\frac{k}{n^2}\cos(nt)\sin(kt)+\frac{k^2}{n^2}I \\ = & \frac{n^2}{n^2-k^2} \left(\frac{1}{n}\sin(nt)\cos(kt)-\frac{k}{n^2}\cos(nt)\sin(kt)\right) \end{align}

what was done wrong here? It can't be true because even if i take $\int_{-\pi}^{\pi}$ the denominator will go to $0$ for $n=k$ then why do they write $2\pi$ ?

share|cite|improve this question
up vote 1 down vote accepted

Hint: For $n=0$ the antiderivative of $\cos(nt)$ is not $\frac{1}{n} \sin(nt)$. You'll need to make a separate calculation for this case.

share|cite|improve this answer


You can "linearize" the integrands by means of the formulae

$$\eqalign{2\cos x\cos y&=\cos(x+y)+\cos(x-y)\ ,\cr 2\cos x\sin y&=\sin(x+y)-\sin(x-y)\ ,\cr 2\sin x\sin y&=\cos(x-y)-\cos(x+y)\ .\cr}$$

share|cite|improve this answer
$$e^{i(x+y)}=cos(x+y)+isin(x+y)=e^{ix}e^{iy}= (cos(x)+isin(x))(cos(y)+isin(y)= cos(x)cos(y)+icos(x)sin(y)+isin(x)cos(y)-sin(x)sin(y)$$ and $$e^{i(x-y)} = cos(x-y)+isin(x-y) = e^{ix}\cdot e^{-iy} =(cos(x)+isin(x))(cos(-y)+isin(-y)) = (cos(x)+isin(x))(cos(y)-isin(y)) = cos(x)cos(y)-icos(x)sin(y)+isin(x)cos(y)+sin(x)sin(y) $$ ? – bakabakabaka Jan 28 '13 at 13:32

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.